Engineering a home-based vertical farm with sensor monitoring - Lee, Hazel Su Fang (Nanyang Technological University, 2024)
Vertical farming has been gaining popularity because it addresses challenges like land scarcity and environmental issues. The increase of home-based vertical farming is an optimistic avenue to enhance the accessibility and inclusivity of sustainable agricultural practices through technological innovations in limited spaces. This Final Year Project (FYP) chronicles the development of VFarm, which is user-friendly and a home-based vertical farming system, integrated and interfaced with Arduino and sensors – sensors include light, temperature, humidity, potential of hydrogen (pH) and electrical conductivity. The initial setback in the development of VFarm lay achieving a balance between simplicity and functionality. Through iterative methods – incorporating design specifications, functional analysis, and morphological chart, VFarm was conceived. This model encapsulated user-friendliness and encompassed technology to optimize plant growth. Integrating sensor monitoring technology involved careful selection and data interpretation to ensure accuracy and user comprehension. The final design allows Arduino to capture real-time environmental data, informing users of the conditions of current light, temperature, and humidity catered to leafy greens. Similar methodologies were applied to Potential of Hydrogen (pH) sensors and Electrical Conductivity (EC) sensors, extending VFarm’s versatility. While VFarm joins an expanding field of vertical farming solutions, its focus on user-friendliness and integrated sensor monitoring sets it apart from other home-based vertical farms. This balance between technology and ease of use encourages individuals to cultivate their own produce in a sustainable manner.